2022
DOI: 10.12997/jla.2022.11.2.111
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ and Vascular Dysfunction: From Mechanisms to Therapeutic Opportunities

Abstract: Nicotinamide adenine dinucleotide (NAD + ) is an essential and pleiotropic coenzyme involved not only in cellular energy metabolism, but also in cell signaling, epigenetic regulation, and post-translational protein modifications. Vascular disease risk factors are associated with aberrant NAD + metabolism. Conversely, the therapeutic increase of NAD + levels through the administration of NAD + precursors or inhibitors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…NAD + has been shown to reduce chronic inflammation, reactivate autophagy, and assist mitochondrial biogenesis. These findings suggest that supplementing with precursor NAD+ may be a useful therapeutic approach for treating these conditions [97], as we have done for our elderly patients long before the pandemic. Further research is required before recommending the use of precursor NAD+ to reduce the severity and mortality of COVID-19 patients.…”
Section: Vitamin B3 Precursor Of Nad +mentioning
confidence: 69%
“…NAD + has been shown to reduce chronic inflammation, reactivate autophagy, and assist mitochondrial biogenesis. These findings suggest that supplementing with precursor NAD+ may be a useful therapeutic approach for treating these conditions [97], as we have done for our elderly patients long before the pandemic. Further research is required before recommending the use of precursor NAD+ to reduce the severity and mortality of COVID-19 patients.…”
Section: Vitamin B3 Precursor Of Nad +mentioning
confidence: 69%
“…Previous studies have reported that ischemia in cardiomyocytes resulted in NAD + depletion, reduced available ATP, and mitochondrial dysfunction [ 65 ]. Supplementation of nicotinic acid restored NAD + balance, improved abnormal blood flow conditions and alleviated ischemia–reperfusion injury [ 66 ]. Similarly, NAD + levels showed a significant decrease in different types of DCM [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sirt3 is a NAD + -dependent deacetylase predominantly located in mitochondria [ 32 ]. Enzymatic activity of Sirt3 is reduced by mitochondrial dysfunction due to repressed mitochondrial NAD + levels, leading to dysregulation of mechanisms for mitochondrial homeostasis maintenance [ 33 , 34 ]. Meanwhile, impaired mitochondrial function affects the utilization of acetyl-CoA in mitochondria, leading to the accumulation of acetyl-CoA in mitochondria, which impairs the function of mitochondrial proteins, such as SOD2 [ 35 ], through nonenzymatic acetylation modification [ 36 ].…”
Section: Discussionmentioning
confidence: 99%